1998
DOI: 10.1182/blood.v91.4.1469
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bleeding After Bone Marrow Transplantation (BMT)— Incidence and Effect on Survival. A Quantitative Analysis in 1,402 Patients

Abstract: Acute bleeding after bone marrow transplantation (BMT) was investigated in 1,402 patients receiving transplants at Johns Hopkins Hospital between January 1, 1986 and June 30, 1995. Bleeding categorization was based on daily scores of intensity used by the blood transfusion service. Moderate and severe episodes were analyzed for bleeding sites. Analysis of the cause of death and the interval of the bleeding episode to outcome endpoints was recorded. Survival estimates were computed for 1,353 BMT patients. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(64 citation statements)
references
References 48 publications
3
57
2
2
Order By: Relevance
“…[79][80][81]84 Respiratory failure requiring mechanical ventilation occurs in most cases, and overall mortality ranges from 64% to 100%. 52,82,85,86 High-dose systemic corticosteroids and supportive care that may include platelet transfusions are standard; procoagulant therapies had variable success in small studies and are not routinely used. 59,60,87,88 Delayed Pulmonary Toxicity Syndrome Delayed pulmonary toxicity syndrome is a subtype of IPS that only occurs after autologous HCT.…”
Section: Diffuse Alveolar Hemorrhagementioning
confidence: 99%
“…[79][80][81]84 Respiratory failure requiring mechanical ventilation occurs in most cases, and overall mortality ranges from 64% to 100%. 52,82,85,86 High-dose systemic corticosteroids and supportive care that may include platelet transfusions are standard; procoagulant therapies had variable success in small studies and are not routinely used. 59,60,87,88 Delayed Pulmonary Toxicity Syndrome Delayed pulmonary toxicity syndrome is a subtype of IPS that only occurs after autologous HCT.…”
Section: Diffuse Alveolar Hemorrhagementioning
confidence: 99%
“…10,11 The potential role of endothelial damage in relation to increased PLT consumption in nonimmunologic PLT transfusion failure has been suggested by several authors. 3,8,11 In a large study comprising 1402 patients after marrow transplantation, Nevo and colleagues 12 found that bleeding was significantly associated with reduced survival, independent of type of transplantation, stem cell source, and diagnosis. They conclude that the bleeding complications may be regarded as a marker of multifactorial clinical deterioration.…”
mentioning
confidence: 99%
“…Although bleeding is not often a direct cause of death in hematopoietic stem cell transplantation, bleeding is associated with significantly reduced survival after HSCT. 32,33 In an interesting analysis using data from their earlier study, Nevo and coworkers 34 found that a cohort of nonbleeding profoundly thrombocytopenic HSCT recipients had an increased early mortality within 100 days after stem cell infusion and reduced overall survival out to 36.5 months. Not surprisingly, the number of profoundly thrombocytopenic patients (four or more PLT counts Յ10 ¥ 10 9 /L) was higher in the study period using the more restrictive transfusion trigger of 10 ¥ 10 9 /L compared to the period using a trigger of 20 ¥ 10 9 /L.…”
Section: Safety Of Stringent Prophylactic Plt Transfusion Policies Inmentioning
confidence: 99%